Investor attention and Portuguese stock market volatility: we’ll google it for you! - Brochado, A. (Cadernos do Mercado de Valores Mobiliários, 2020)
The importance of investor attention in financial markets is well established on a theoretical level (e.g. Merton, 1987; Hirshleifer and Teoh, 2003; Sims, 2003), and several proxies for investor attention have already been proposed (e.g. Barber and Odean, 2008). More recently, Da et al. (2014) conducted one of the first studies to incorporate Internet search behaviour as a proxy for retail investors’ attention allocation. This approach recognises that the Internet has become a mainstream platform for the production, intermediation and consumption of information in the financial industry. Search engines are an intuitive research tool that provides access to huge amounts of information at a negligible cost. Investors consider information attention a valuable cognitive resource (Zhang et al., 2013), and investors who pay attention to stock or market indices habitually search for new information about them. Weng et al. (2018) maintain that Google search data, in particular, capture traders’ collective interest.